A bicoherence-based nonlinearity measurement method for identifying the location of breathing cracks in blades. (October 2021) - Jiang, Mian; Wang, Daoyong; Kuang, Yingwei; Mo, Xianxian
Abstract: In the assessment of breathing cracks, it is assumed that both sides of the crack will contact each other along with the vibration, causing the blades to exhibit nonlinear behaviors. Therefore, nonlinear approaches are much more sensitive to the cracks and are also capable of detecting their location and size. Recently, a nonlinearity measure-based damage location method was proposed for the distributed vibration responses of beam-like structures. However, its procedures require collecting the trajectories of the non-destructive status of structures, which introduce substantial difficulties to engineering applications. In this paper, a bicoherence-based nonlinearity measurement method is proposed for identifying the location of breathing cracks in blades. It can evaluate the extent of nonlinearity in the responses of blades under random excitations and avoids using the non-destructive status of structures. The additional nonlinearity in a blade with a breathing crack, based on distributed parameter modeling, is discussed, while the distributed responses on characteristic point were collected to estimate the degree of nonlinearity. A Total Nonlinearity Index (TNLI) was used to establish the damage indicator of the blade, and the crack was identified by finding the maximum components. Validation experiments were conducted to verify the effectiveness of the proposed method, in which a vision measurement system was employed to obtain the distributed vibration responses. Highlights: A bicoherence-based nonlinearity measurement method is proposed for cracks location. The method evaluates the extent of nonlinearity in blades under random excitations. The method can avoid using the non-destructive status of structures to locate the crack.